PHOTODEGRADATION OF METHYL RED USING Cd-Al/C LAYERED DOUBLE HYDROXIDE CATALYST (FUDMA JOURNAL OF SCIENCES, 2020)
This paper evaluate the degradation of Methyl Red using cadmium aluminum carbon (Cd-Al/C) catalyst under visible light irradiation. The catalyst was successfully prepared from cadmium fluoride (CdF2), aluminium chloride (AlCl3), and rice husks activated carbon, and then characterized by using X-ray Diffraction (XRD), Scaning Electron Microscopy (SEM) and Fourier Transform Infrared (FTIR) techniques. The peaks at 23.4 and 35.5 in the XRD result confirmed the presences of LDH. The effect of contact time, catalyst dosage, pH and initial concentration, on the photodegradiation of Methyl Red were investigated. The experimental results showed that after 100 min visible light irradiation, the percentage degradation using 200 mg Cd-Al/C, pH 7 and 3 ppm Methyl Red concentration reached to 83.80%. For kinetics studies the data obtained were analyzed using pseudo first order and pseudo second order kinetic models.  From the linear regression coefficient values the data were found to be best fitted to pseudo second order kinetics. The results revealed that the Cd-Al/C show good catalytic activity
Keywords: Photodegradation, Layered Double Hydroxide (LDH) Cadnium fluoride, Aluminium Chloride and Methyl Red